2021
DOI: 10.3389/fcimb.2021.647220
|View full text |Cite
|
Sign up to set email alerts
|

Subunit Vaccine ESAT-6:c-di-AMP Delivered by Intranasal Route Elicits Immune Responses and Protects Against Mycobacterium tuberculosis Infection

Abstract: Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb) infection, remains the most common cause of death from a single infectious disease. More safe and effective vaccines are necessary for preventing the prevalence of TB. In this study, a subunit vaccine of ESAT-6 formulated with c-di-AMP (ESAT-6:c-di-AMP) promoted mucosal and systemic immune responses in spleen and lung. ESAT-6:c-di-AMP inhibited the differentiations of CD8+ T cells as well as macrophages, but promoted the differentiations of ILCs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…The respiratory tract is the natural route of Mtb infection. Therefore, when compared with traditional parenteral routes of vaccination, there is general agreement that mucosal vaccination induces superior protection against Mtb challenge (Goonetilleke et al, 2003;Chen et al, 2004;Wang et al, 2004;Santosuosso et al, 2005;Perdomo et al, 2016;Mata et al, 2021;Ning et al, 2021). The successful formulation and manufacture of the prophylactic TB vaccine (ID93) co-lyophilized with the GLA-SE oil-in-water emulsion adjuvant produced a thermostable, single-vial candidate product that is being evaluated in an ongoing clinical trial as a reconstituted IM vaccine (Kramer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory tract is the natural route of Mtb infection. Therefore, when compared with traditional parenteral routes of vaccination, there is general agreement that mucosal vaccination induces superior protection against Mtb challenge (Goonetilleke et al, 2003;Chen et al, 2004;Wang et al, 2004;Santosuosso et al, 2005;Perdomo et al, 2016;Mata et al, 2021;Ning et al, 2021). The successful formulation and manufacture of the prophylactic TB vaccine (ID93) co-lyophilized with the GLA-SE oil-in-water emulsion adjuvant produced a thermostable, single-vial candidate product that is being evaluated in an ongoing clinical trial as a reconstituted IM vaccine (Kramer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…c-di-AMP could induce innate immune responses and enhance antigen-induced Th1/Th2/Th17 responses as an adjuvant ( Ebensen et al, 2011 ; Devaux et al, 2018 ; Ning et al, 2021 ). It has been revealed that M. tuberculosis Δ cnpB could trigger host innate immune responses, which could promote the clearance of bacteria ( Yang et al, 2014 ; Dey et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Now, c-di-AMP has been considered a key mycobacterial pathogen-associated molecular pattern (PAMP) inducing host innate immune responses, including type I IFN response and autophagy ( Woodward et al, 2010 ; Dey et al, 2015 ; Devaux et al, 2018 ; Ning et al, 2019 ; Singh et al, 2022 ). Additionally, c-di-AMP as an adjuvant enhanced antigen-induced Th1/Th2/Th17 pattern responses ( Ebensen et al, 2011 ; Ning et al, 2021 ). It has been noted that cnpB -deleted strain of M. tuberculosis triggered a potent type I IFN response, showing the reduction of bacillary burden in the mouse model, implying virulence attenuation in M. tuberculosis ( Yang et al, 2014 ; Dey et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…ESAT-6 has been shown to inhibit autophagic flux by impeding autophagosome-lysosome fusion in ex vivo cell culture, which assists in Mtb immune escape from macrophages (220)(221)(222). Preclinical studies in Balb/c mice show that vaccination with ESAT-6 and c-di-AMP regulate macrophage autophagy, resulting in the inhibition of Mtb growth in macrophages during early infection (223).…”
Section: Monocytes/macrophagesmentioning
confidence: 99%